Exploring the Role of Professional Accountants in Enhancing Public Value through Financial Transparency and Accountability in the Nigerian Public Sector - Awe, Solomon Olurotimi; Abiloro, Rofiyat Bosede; Oyebanji, Azeez Abiola (Acta Universitatis Danubius. Œconomica, 2025)
This study explores the role of professional accountants in creating public value in the Nigerian public sector, focusing on their contributions to financial transparency, resource allocation efficiency, and public accountability. It aims to highlight the significance of accounting professionals in strengthening public financial management and governance. The research builds on existing literature that emphasizes the importance of professional accountants in ensuring financial integrity and good governance within public institutions. It addresses the gap in empirical evidence on how these professionals influence public value outcomes in emerging economies. A mixed-methods approach was adopted. Quantitative data were collected through structured questionnaires administered to 309 selected accountants and financial officers across Nigerian Ministries, Departments, and Agencies, with 270 valid responses. Additionally, qualitative insights were obtained through in-depth interviews with 20 senior accountants and auditors. Data was analyzed using descriptive statistics and regression analysis. The findings revealed that professional accountants significantly contribute to public value creation by promoting financial transparency, enabling efficient resource utilization, and strengthening accountability mechanisms. The study offers policy and managerial insights for enhancing the roles of accountants in public sector governance. This paper provides original empirical evidence on the impact of professional accounting practices in advancing public value in Nigeria’s public sector.